Manajemen Pondok Pesantren dalam Pengelolaan Sumber Daya Manusia terhadap Peningkatan Kemampuan Santri (Studi pada Pondok Pesantren Darul Qur'an Kota Malang) - Widodo, Wahyudi (Lembaga Yasin AlSys, 2025)
Human resources in pesantren management are very necessary in order to achieve good goals and also be able to face all future challenges, especially for students. The purpose of this writing is to discuss the management of Islamic boarding schools in human resource management to improve the ability of students. The research used used a qualitative type with a descriptive approach for three months. The results of the study show that, in the management of the Darul Quran Islamic Boarding School Malang human resources can be divided into two things management. The first is the management of managerial functions, namely planning related to pesantren and improving student human resources with Visions, Missions and goals, organizing that folds all administrators and community leaders, movements related to activities commanded by caregivers so that one direction of goals, and control or evaluation. The second of the operational functions is the procurement of things needed by students, development in all aspects of facilities, programs, assessments that focus on students' abilities, integration between religious and real-life aspects, discipline of all administrators and students, and dismissal of administrators who do not carry out their activities to improve students' human resources. The form of activities such as: level-based book recitation, trainings on religious skills and the science of world life, cooperation in various aspects of additional activities to scientific visits.